2017
DOI: 10.1176/appi.ajp.2016.16050503
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Resistant Schizophrenia: Treatment Response and Resistance in Psychosis (TRRIP) Working Group Consensus Guidelines on Diagnosis and Terminology

Abstract: Objective Treatment resistance complicates the management of schizophrenia. Research and clinical translation is limited by inconsistent definitions. To address this we evaluated current approaches and then developed consensus criteria and guidelines. Method A systematic review of randomized antipsychotic clinical trials in treatment resistant schizophrenia was performed. Definitions of treatment resistance were extracted. Subsequently, consensus operationalized criteria were developed by a working group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
756
1
29

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 821 publications
(796 citation statements)
references
References 93 publications
10
756
1
29
Order By: Relevance
“…The patient was diagnosed with treatment-resistant schizophrenia (TRS) according to TRS guidelines (insufficient response to at least two sequential, different antipsychotic medications of adequate doses taken over an adequate time period) [30, 31] after these two antipsychotic medications were found to be ineffective, and was therefore treated with clozapine monotherapy which was gradually increased to 600 mg daily (clozapine and norclozapine blood levels were in the normal range). Psychotic symptomatology initially improved, but persecutive thoughts and anxiety reappeared.…”
Section: Case Reportmentioning
confidence: 99%
“…The patient was diagnosed with treatment-resistant schizophrenia (TRS) according to TRS guidelines (insufficient response to at least two sequential, different antipsychotic medications of adequate doses taken over an adequate time period) [30, 31] after these two antipsychotic medications were found to be ineffective, and was therefore treated with clozapine monotherapy which was gradually increased to 600 mg daily (clozapine and norclozapine blood levels were in the normal range). Psychotic symptomatology initially improved, but persecutive thoughts and anxiety reappeared.…”
Section: Case Reportmentioning
confidence: 99%
“…This study strengthened several previous findings, including the largest association with the major histocompatibility complex locus on chromosome 6, involvement of an N-methyl-D-aspartate (NMDA) receptor (GRIN2A) with other glutamatergic genes, and the DRD2 gene—the D 2 receptor is an essential target of antipsychotics 43. Discovered in 1950, antipsychotics are proven effective at treating psychosis and their mechanism of action provides insight into aspects of the molecular underpinnings of psychosis 6. The finding that mean doses of different antipsychotics were correlated with their binding affinity for D 2 demonstrated how essential D 2  binding is to antipsychotic action 44…”
Section: Methodsmentioning
confidence: 99%
“…Most antipsychotics have similar efficacy with the exception of clozapine, a notably more effective antipsychotic used in treatment-resistant patients 6. Relapse is a critical barrier to optimal recovery and 61%–82% of patients with SZ experience a relapsing and remitting disease course 1 7.…”
Section: Current State Of Treatment For Schizophreniamentioning
confidence: 99%
“…In effect, the results of any trial of any drug in 'refractory (or resistant) schizophrenia' are substantially dependent on what that term means. An analysis of 42 studies [26] found that half did not provide details of how treatment resistance was defined and only two (5%) of the remainder used the same criteria.…”
Section: ó Springer International Publishing Switzerland 2017mentioning
confidence: 99%